Enhanced corrosion protection of AZ31B magnesium alloy by MgAl-LDHs composite coatings double-doped with imidazolium ionic liquid and sodium dodecylbenzenesulphonate. (3rd April 2023) - Liu, Yingxue; Huangfu, Huijie; Gao, Shuai; Guo, Xugeng; Wang, Li
ABSTRACT: Herein, we prepare two types of MgAl-LDHs coatings single-doped by imidazolium ionic liquid 1-decyl-3-methylimidazolium bromide ([Demim]Br) or sodium dodecylbenzenesulphonate (SDBS) and double-doped by [Demim]Br and SDBS on AZ31B Mg alloy by using an in-situ hydrothermal treatment. Their surface morphology and corrosion resistance immersed in 3.5 wt-% NaCl solution are explored. Our results suggest that the double doping of [Demim]Br and SDBS will change the surface morphology of the coating and a uniform and dense film is observed in the double-doped MgAl-LDHs, which is denser than those of the two single-doped MgAl-LDHs coatings, thus providing a superior corrosion resistance. Such an improvement can be ascribed to the synergetic inhibition effect of [Demim]Br and SDBS against the corrosion of the Mg alloy substrate. More importantly, the charge transfer resistance of the sample coated with the double-doped MgAl-LDHs is still high after 3 d of immersion, benefiting from the excellent self-healing effect.